Impact of Climate Change in Zimbabwe - Mark Matsa (Springer, Cham, 2023)
The chapter identifies and evaluates constraints encountered by farming communities in coping with climate change and variability in different parts of the country. It reviews and analyses government position on climate change. It evaluates communities’ awareness of climate change and assesses the impact of government programmes at community level. Development initiatives by government and non-governmental organisations in south-western districts are also discussed. The last part of the chapter identifies and discusses post-independence development policies adopted by government and relates them to south-western Zimbabwe. Sources of data for the chapter are mainly scientific literature, government policy documents and related documents. The rational for the chapter is to contextualise the book, putting the study area into perspective.